Enhancing Product Quality, Consistency, And Food Safety of Culinary MSMES Through Practice-Based Cooking Skills Training - Kristian Agung Nugraha; Johan Pratama Siahainenia; Hari Minantyo; Fabiola Leoparjo; Devina Irtanto; Victor Kurniawan Yuwono; Devi Rahnjen Wijayadne (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2026)
Departing from the strategic role of culinary MSMEs as a driver of the local economy as well as the challenge of low quality consistency and food safety standards faced by business actors in Lontar Village, this service research aims to improve the quality of MSME products through the development of culinary skills based on practicum training. The program was carried out using a descriptive-qualitative approach involving ten MSME actors who were selected purposively, through a series of activities in the form of initial observation, knowledge transfer, cooking practicum, intensive mentoring, and pre- and post-intervention evaluation. The results of the study showed a significant increase in taste quality, product consistency, mastery of food processing techniques, selection and handling of raw materials, and the application of food safety and hygiene practices, which overall strengthened the readiness of MSMEs to compete in local and modern markets. These findings confirm that a contextual and applicative practice-based training approach is more effective in building the capacity of MSMEs than a theoretical approach alone. The implications of this study show that the development of culinary skills and food safety standards need to be positioned as a core strategy in the policy of fostering regional MSMEs, because it not only increases the competitiveness of products, but also builds the foundation of business sustainability and strengthening the local economy in an inclusive manner.Berangkat dari peran strategis UMKM kuliner sebagai penggerak ekonomi lokal sekaligus tantangan rendahnya konsistensi kualitas dan standar keamanan pangan yang dihadapi pelaku usaha di Desa Lontar, penelitian pengabdian ini bertujuan untuk meningkatkan kualitas produk UMKM melalui pengembangan keterampilan kuliner berbasis pelatihan praktikum. Program ini dilaksanakan dengan menggunakan pendekatan deskriptif-kualitatif, melibatkan 10 pelaku UMKM yang dipilih secara purposif melalui serangkaian kegiatan, meliputi observasi awal, transfer pengetahuan, praktikum memasak, pendampingan intensif, serta evaluasi pra dan pasca intervensi. Hasil penelitian menunjukkan adanya peningkatan signifikan pada kualitas rasa, konsistensi produk, penguasaan teknik pengolahan makanan, pemilihan dan penanganan bahan baku, serta penerapan praktik keamanan dan higienitas pangan, sehingga memperkuat kesiapan UMKM untuk bersaing di pasar lokal maupun modern. Temuan ini menegaskan bahwa pendekatan pelatihan berbasis praktik yang kontekstual dan aplikatif lebih efektif dalam membangun kapasitas UMKM dibandingkan pendekatan teoretis semata. Implikasi penelitian ini menunjukkan bahwa pengembangan keterampilan kuliner dan standar keamanan pangan perlu diposisikan sebagai strategi inti dalam kebijakan pembinaan UMKM daerah, karena tidak hanya meningkatkan daya saing produk, tetapi juga membangun fondasi keberlanjutan usaha serta memperkuat perekonomian lokal secara inklusif.